Preparation of hydroximic acid functionalized UiO-66-(COOH) 2 fiber membrane adsorbent and application of hydroximic acid functionalized UiO-66-(COOH) 2 fiber membrane adsorbent in gallium adsorption

By functionalizing UiO-66-(COOH)2 and preparing PAN/UiO-66-HA fiber membrane adsorbent, the existing adsorbents have solved the problem of poor adsorption effect of gallium ion and difficult to recover in powder form, and achieved efficient, selective and easy-to-recover gallium ion adsorption effect.

CN119701907AActive Publication Date: 2025-03-28ZHENGZHOU UNIV

Patent Information

Application Number
CN202510182621.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-28
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The adsorption effect of the existing UiO-66-(COOH)2 adsorbent on gallium ions is average, and the powdered adsorbent is not easy to recover.

Method used

UiO-66-(COOH)2 was functionalized by hydroxamic acid, and the adsorbent PAN/UiO-66-HA in the form of a fiber membrane was prepared, and the membrane-like adsorbent was prepared by electrospinning technology.

Benefits of technology

The adsorbent can efficiently adsorb trace gallium ions under acidic conditions, have high selective adsorption rates and fast adsorption rates, and is easy to recover and recycle due to the fiber membrane form.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701907A_ABST
    Figure CN119701907A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydroxamic acid functionalized UiO-66-(COOH) 2 fiber membrane adsorbent, and belongs to the technical field of hydroxamic acid adsorbent preparation, and the preparation method comprises the following steps: S1, preparing UiO-66-(COOH) 2; s2, UiO-66-COOCH3 is prepared, and the UiO-66- S3, preparing UiO-66-HA (hyaluronic acid); s4, a PAN / UiO-66-HA membrane is prepared; the PAN / UiO-66-HA membrane prepared by the method has the characteristics that the preparation is easy, the preparation process is green and environment-friendly, gallium ions can be adsorbed from a trace gallium solution under an acidic condition, the selective adsorption rate is high, the adsorption rate is high, and the PAN / UiO-66-HA membrane is easy to recycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of hydroxamic acid adsorbents, and specifically relates to the preparation of a hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent and its application in adsorbing gallium. Background Art

[0002] Gallium is listed as a strategic metal by China, the United States, the European Union and other countries. It is a "high-tech element" of high-tech industries and is widely used in electronic communications, new energy, chips, low-melting-point alloys, military industry and other fields.

[0003] Gallium has an abundance of only 17 mg / L in the earth's crust. It is a typical rare metal and most of it exists in the form of associated minerals, making the extraction of gallium ions more difficult.

[0004] At present, the methods for extracting gallium generally include ion exchange, solvent extraction, chlorination separation, electrodeposition separation and adsorption. Among them, ion exchange, solvent extraction, chlorination separation and electrodeposition separation will produce harmful gases, high cost and unstable separation process during the extraction process. Therefore, adsorption extraction is more widely used.

[0005] Metal-organic framework materials are widely used in adsorption methods due to their high specific surface area, adjustable pore structure and abundant active sites.

[0006] Although UiO-66-(COOH)2 is a type of metal-organic framework material, its adsorption effect on gallium ions is average due to its single active site, and the powdered adsorbent is not easy to recycle.

[0007] In view of this, the preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent and its application in the adsorption of gallium were designed to solve the above problems. Summary of the invention

[0008] To solve the problems raised in the above background technology. The present invention provides the preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent and its application in adsorbing gallium, which has the characteristics of easy preparation, green and environmentally friendly preparation process, adsorption of gallium ions from trace gallium solution under acidic conditions, high selective adsorption rate, fast adsorption rate and easy recycling of powder materials.

[0009] To achieve the above object, the present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0010] S1: Preparation of UiO-66-(COOH)2

[0011] Zirconium tetrachloride and pyromellitic acid were dispersed in deionized water, stirred at room temperature, and then refluxed to obtain a white gel, centrifuged, and washed with deionized water to obtain a solid. The solid was dispersed in deionized water, then refluxed to obtain a product, centrifuged, washed with deionized water, and then dried in vacuo to obtain UiO-66-(COOH)2;

[0012] S2: Preparation of UiO-66-COOCH3

[0013] The prepared UiO-66-(COOH)2 was added to a 100 mL round-bottom flask, and methanol and trimethylsilane were added, and the mixture was heated to react to obtain a solid powder, which was then washed with ethanol and deionized water and dried in vacuo to obtain UiO-66-COOCH3;

[0014] S3: Preparation of UiO-66-HA

[0015] The prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to react, and a solid was obtained, which was washed with ethanol and deionized water, and vacuum dried to obtain UiO-66-HA;

[0016] S4: Preparation of PAN / UiO-66-HA membrane

[0017] PAN was dissolved in DMF, and then the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to obtain a spinning solution, which was then electrospun to obtain a PAN / UiO-66-HA membrane.

[0018] Furthermore, in step S1, the amount of zirconium tetrachloride added is 2.3 g, the amount of pyromellitic acid added is 4.3 g, and the amount of deionized water added is 50 mL.

[0019] Furthermore, in step S1, the reflux heating temperature is 100° C. and the heating time is 24 hours.

[0020] Furthermore, in step S2, the amount of prepared UiO-66-(COOH)2 added is 2 g, the amount of methanol added is 40 mL, and the amount of trimethylsilane added is 3 mL.

[0021] Furthermore, in step S3, the added amount of the prepared UiO-66-COOCH3 is 1.5 g.

[0022] Furthermore, in the steps S2 and S3, the heating temperature of the heating reaction is 70° C. and the reaction time is 10 h.

[0023] Furthermore, in the steps S1, S2 and S3, the vacuum drying temperature is 60°C and the drying time is 24 hours.

[0024] Furthermore, in step S4, the amount of PAN added is 1.0 g, the amount of DMF added is 10 mL, and the amount of UiO-66-HA added is 0.8 g.

[0025] Furthermore, in step S4, the voltage of electrospinning is 13KV and the flow rate is 5μL min -1 .

[0026] The prepared hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent is used in adsorbing gallium.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The PAN / UiO-66-HA membrane prepared by the present invention has the characteristics of being easy to prepare, having a green and environmentally friendly preparation process, being able to adsorb gallium ions from a trace gallium solution under acidic conditions, having a high selective adsorption rate, a fast adsorption rate, and being easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The infrared, XRD and SEM images of UiO-66-HA of the present invention are shown;

[0030] Figure 2 This is the SEM image of the PAN / UiO-66-HA fiber membrane of the present invention;

[0031] Figure 3 It is a static adsorption test result diagram of the PAN fiber membrane and the PAN / UiO-66-HA fiber membrane of the present invention;

[0032] Figure 4 This is a graph showing the water flux experimental results of the PAN / UiO-66-HA fiber membrane at a ratio of 4:5 according to the present invention;

[0033] Figure 5 This is a graph showing the selectivity experimental results of the PAN / UiO-66-HA fiber membrane at a ratio of 4:5 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1

[0036] The present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0037] S1: Preparation of UiO-66-(COOH)2

[0038] Take 2.3g zirconium tetrachloride and 4.3g pyromellitic acid and disperse them in 50mL deionized water, stir at room temperature, and then reflux and heat at 100℃ for 24h to obtain a white gel, centrifuge, and wash with deionized water for more than five times to obtain a solid. Disperse the solid in 50mL deionized water, then reflux and heat at 100℃ for 24h to obtain the product, centrifuge, wash with deionized water to obtain a solid, and vacuum dry at 60℃ for 24h to obtain UiO-66-(COOH)2;

[0039] S2: Preparation of UiO-66-COOCH3

[0040] Take 2 g of the prepared UiO-66-(COOH)2 and add it to a 100 mL round-bottom flask, then add 40 mL of methanol and 3 mL of trimethylsilane, heat to 70 ° C and react for 10 h to obtain a solid powder, wash with ethanol and deionized water, and vacuum dry at 60 ° C for 24 h to obtain UiO-66-COOCH3;

[0041] S3: Preparation of UiO-66-HA

[0042] 1.5 g of the prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to 70°C for reaction for 10 h to obtain a solid, washed with ethanol and deionized water, and vacuum dried at 60°C for 24 h to obtain UiO-66-HA;

[0043] S4: Preparation of PAN / UiO-66-HA membrane

[0044] 1.0 g PAN was dissolved in 10 mL DMF, and then 0.2 g of the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to prepare the spinning solution. -1 PAN / UiO-66-HA membrane was prepared by electrospinning at a flow rate of 40.5 %.

[0045] Embodiment 2

[0046] The present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0047] S1: Preparation of UiO-66-(COOH)2

[0048] Take 2.3g zirconium tetrachloride and 4.3g pyromellitic acid and disperse them in 50mL deionized water, stir at room temperature, and then reflux and heat at 100℃ for 24h to obtain a white gel, centrifuge, and wash with deionized water for more than five times to obtain a solid. Disperse the solid in 50mL deionized water, then reflux and heat at 100℃ for 24h to obtain the product, centrifuge, wash with deionized water to obtain a solid, and vacuum dry at 60℃ for 24h to obtain UiO-66-(COOH)2;

[0049] S2: Preparation of UiO-66-COOCH3

[0050] Take 2 g of the prepared UiO-66-(COOH)2 and add it to a 100 mL round-bottom flask, then add 40 mL of methanol and 3 mL of trimethylsilane, heat to 70 ° C and react for 10 h to obtain a solid powder, wash with ethanol and deionized water, and vacuum dry at 60 ° C for 24 h to obtain UiO-66-COOCH3;

[0051] S3: Preparation of UiO-66-HA

[0052] 1.5 g of the prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to 70°C for reaction for 10 h to obtain a solid, washed with ethanol and deionized water, and vacuum dried at 60°C for 24 h to obtain UiO-66-HA;

[0053] S4: Preparation of PAN / UiO-66-HA membrane

[0054] 1.0 g PAN was dissolved in 10 mL DMF, and then 0.4 g of the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to prepare the spinning solution. -1 PAN / UiO-66-HA membrane was prepared by electrospinning at a flow rate of 40.5 %.

[0055] Embodiment 3

[0056] The present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0057] S1: Preparation of UiO-66-(COOH)2

[0058] Take 2.3g zirconium tetrachloride and 4.3g pyromellitic acid and disperse them in 50mL deionized water, stir at room temperature, and then reflux and heat at 100℃ for 24h to obtain a white gel, centrifuge, and wash with deionized water for more than five times to obtain a solid. Disperse the solid in 50mL deionized water, then reflux and heat at 100℃ for 24h to obtain the product, centrifuge, wash with deionized water to obtain a solid, and vacuum dry at 60℃ for 24h to obtain UiO-66-(COOH)2;

[0059] S2: Preparation of UiO-66-COOCH3

[0060] Take 2 g of the prepared UiO-66-(COOH)2 and add it to a 100 mL round-bottom flask, then add 40 mL of methanol and 3 mL of trimethylsilane, heat to 70 ° C and react for 10 h to obtain a solid powder, wash with ethanol and deionized water, and vacuum dry at 60 ° C for 24 h to obtain UiO-66-COOCH3;

[0061] S3: Preparation of UiO-66-HA

[0062] 1.5 g of the prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to 70°C for reaction for 10 h to obtain a solid, washed with ethanol and deionized water, and vacuum dried at 60°C for 24 h to obtain UiO-66-HA;

[0063] S4: Preparation of PAN / UiO-66-HA membrane

[0064] 1.0 g PAN was dissolved in 10 mL DMF, and then 0.6 g of the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to prepare the spinning solution. -1 PAN / UiO-66-HA membrane was prepared by electrospinning at a flow rate of 40.5 %.

[0065] Embodiment 4

[0066] The present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0067] S1: Preparation of UiO-66-(COOH)2

[0068] Take 2.3g zirconium tetrachloride and 4.3g pyromellitic acid and disperse them in 50mL deionized water, stir at room temperature, and then reflux and heat at 100℃ for 24h to obtain a white gel, centrifuge, and wash with deionized water for more than five times to obtain a solid. Disperse the solid in 50mL deionized water, then reflux and heat at 100℃ for 24h to obtain the product, centrifuge, wash with deionized water to obtain a solid, and vacuum dry at 60℃ for 24h to obtain UiO-66-(COOH)2;

[0069] S2: Preparation of UiO-66-COOCH3

[0070] Take 2 g of the prepared UiO-66-(COOH)2 and add it to a 100 mL round-bottom flask, then add 40 mL of methanol and 3 mL of trimethylsilane, heat to 70 ° C and react for 10 h to obtain a solid powder, wash with ethanol and deionized water, and vacuum dry at 60 ° C for 24 h to obtain UiO-66-COOCH3;

[0071] S3: Preparation of UiO-66-HA

[0072] 1.5 g of the prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to 70°C for reaction for 10 h to obtain a solid, washed with ethanol and deionized water, and vacuum dried at 60°C for 24 h to obtain UiO-66-HA;

[0073] S4: Preparation of PAN / UiO-66-HA membrane

[0074] 1.0 g PAN was dissolved in 10 mL DMF, and then 0.8 g of the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to prepare the spinning solution. -1 PAN / UiO-66-HA membrane was prepared by electrospinning at a flow rate of 40.5 %.

[0075] Embodiment 5

[0076] The present invention provides the following technical solution: Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, comprising the following steps:

[0077] S1: Preparation of UiO-66-(COOH)2

[0078] Take 2.3g zirconium tetrachloride and 4.3g pyromellitic acid and disperse them in 50mL deionized water, stir at room temperature, then reflux and heat at 100℃ for 24h to obtain a white gel, centrifuge, wash with deionized water for more than five times to obtain a solid, disperse it in 50mL deionized water, then reflux and heat at 100℃ for 24h to obtain the product, centrifuge, wash with deionized water to obtain a solid, and vacuum dry at 60℃ for 24h to obtain UiO-66-(COOH)2;

[0079] S2: Preparation of UiO-66-COOCH3

[0080] Take 2 g of the prepared UiO-66-(COOH)2 and add it to a 100 mL round-bottom flask, then add 40 mL of methanol and 3 mL of trimethylsilane, heat to 70 ° C and react for 10 h to obtain a solid powder, wash with ethanol and deionized water, and vacuum dry at 60 ° C for 24 h to obtain UiO-66-COOCH3;

[0081] S3: Preparation of UiO-66-HA

[0082] 1.5 g of the prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to 70°C for reaction for 10 h to obtain a solid, washed with ethanol and deionized water, and vacuum dried at 60°C for 24 h to obtain UiO-66-HA;

[0083] S4: Preparation of PAN / UiO-66-HA membrane

[0084] 1.0 g PAN was dissolved in 10 mL DMF, and then 1.0 g of the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to prepare the spinning solution. -1 PAN / UiO-66-HA membrane was prepared by electrospinning at a flow rate of 40.5 %.

[0085] Comparative Example 1

[0086] The preparation of PAN fiber membrane adsorbent includes the following steps:

[0087] 1.0 g PAN was dissolved in 10 mL DMF and stirred at room temperature until completely dissolved to obtain a spinning solution, which was then electrospun at a voltage of 13 KV and a flow rate of 5 μL min-1 to obtain a PAN fiber membrane.

[0088] The characterization diagram of UiO-66-HA prepared in the embodiment is shown in the attached figure. Figure 1 As shown in the attached Figure 1 It can be seen that: UiO-66-HA powder material is successful and has a large specific surface area;

[0089] The SEM image of the PAN / UiO-66-HA membrane prepared in the embodiment is shown in the attached figure. Figure 2 As shown in the attached Figure 2 It can be seen that the UiO-66-HA powder material is evenly distributed in the fiber membrane;

[0090] Static adsorption experiments were performed on the PAN / UiO-66-HA membranes and PAN fiber membranes prepared in Examples 1 to 5 and Comparative Example 1;

[0091] The static adsorption experiment was performed as follows: 100 mL of a 100 mg / g gallium solution was prepared, and a static adsorption experiment was performed on the PAN / UiO-66-HA membrane and the PAN fiber membrane prepared in Examples 1 to 5 and Comparative Example 1;

[0092] The results of static adsorption experiments are shown in the attached Figure 3 As shown in the attached Figure 3 It can be seen that at the ratio of 4:5, i.e., 0.8 g of PAN / UiO-66-HA membrane, the adsorption rate and adsorption amount were the highest, which were 99% and 260 mg / g, respectively;

[0093] The water flux test was carried out on PAN / UiO-66-HA membrane with a ratio of 4:5, i.e. 0.8 g. The results are shown in the attached figure. Figure 4 As shown in the attached Figure 4 It can be seen that: at a lower water flux, the adsorption rate can reach more than 95%;

[0094] The selectivity test was conducted on PAN / UiO-66-HA membrane at a ratio of 4:5, i.e. 0.8 g. The results are shown in the attached figure. Figure 5 As shown in the attached Figure 5 It can be seen that the adsorption rate of gallium can reach 99% in the coexisting ion solution of Cu, Zn, Al and Ga, which has good selectivity. That is, the prepared hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent has good applicability in the adsorption of gallium.

[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Preparation of hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent, characterized in that: The following steps are involved: S1: Preparation of UiO-66-(COOH)2 Zirconium tetrachloride and pyromellitic acid were dispersed in deionized water, stirred at room temperature, and then refluxed to obtain a white gel, centrifuged, and washed with deionized water to obtain a solid. The solid was dispersed in deionized water, then refluxed to obtain a product, centrifuged, washed with deionized water, and then dried in vacuo to obtain UiO-66-(COOH)2; S2: Preparation of UiO-66-COOCH3 The prepared UiO-66-(COOH)2 was added to a 100 mL round-bottom flask, and methanol and trimethylsilane were added, and the mixture was heated to react to obtain a solid powder, which was then washed with ethanol and deionized water and dried in vacuo to obtain UiO-66-COOCH3; S3: Preparation of UiO-66-HA The prepared UiO-66-COOCH3 was added to the hydroxylamine free liquid, heated to react, and a solid was obtained, which was washed with ethanol and deionized water, and vacuum dried to obtain UiO-66-HA; S4: Preparation of PAN / UiO-66-HA membrane PAN was dissolved in DMF, and then the prepared UiO-66-HA was added and stirred at room temperature until it was completely dissolved to obtain a spinning solution, which was then electrospun to obtain a PAN / UiO-66-HA membrane.

2. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the step S1, the added amount of zirconium tetrachloride is 2.3 g, the added amount of pyromellitic acid is 4.3 g, and the added amount of deionized water is 50 mL.

3. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In step S1, the reflux heating temperature is 100° C. and the heating time is 24 hours.

4. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the step S2, the amount of prepared UiO-66-(COOH)2 added is 2 g, the amount of methanol added is 40 mL, and the amount of trimethylsilane added is 3 mL.

5. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the step S3, the added amount of the prepared UiO-66-COOCH3 is 1.5 g.

6. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the steps S2 and S3, the heating temperature of the heating reaction is 70° C. and the reaction time is 10 h.

7. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the steps S1, S2 and S3, the vacuum drying temperature is 60°C and the drying time is 24 hours.

8. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In the step S4, the amount of PAN added was 1.0 g, the amount of DMF added was 10 mL, and the amount of UiO-66-HA added was 0.8 g.

9. The preparation of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent according to claim 1, characterized in that: In step S4, the voltage of electrospinning was 13 KV and the flow rate was 5 μL min -1 .

10. Use of the hydroxamic acid functionalized UiO-66-(COOH)2 fiber membrane adsorbent prepared according to any one of claims 1 to 9 in the adsorption of gallium.

Citation Information

Patent Citations

  • Method for separating and regenerating organic phase of invalid gallium and germanium extracting agent

    CN113789445A

  • Preparation method of hydroximic acid functionalized chitosan-based gallium ion adsorbent

    CN118085128A

  • Preparation method of hydroximic acid functionalized gallium ion adsorption resin, gallium ion adsorption resin and application

    CN118359746A

  • Gas-storing material including metal / organic framework bonded by hydroxamic acid

    TW202128613A

  • Gas-storing material including metal / organic framework bonded by hydroxamic acid

    US20230056785A1

Cited By

  • A method for selectively separating and extracting gallium

    CN120060672B